The Methuen Drama companion to performance art - Bloomsbury Publishing Plc.; Bloomsbury Publishing Plc; Ferdman, Bertie; Stokic, Jovana (London Bloomsbury Methuen Drama, 2020)
The Methuen Drama Companion to Performance Art offers a comprehensive guide to the major issues and interdisciplinary debates concerning performance in art contexts that have developed over the last decade. It understands performance art as an institutional, cultural, and economic phenomenon rather than as a label or object. Following the ever-increasing institutionalization and mainstreaming of performance, the book's chapters identify a marked change in the economies and labor practices surrounding performance art, and explore how this development is reflective of capitalist approaches to art and event production. Embracing what we perceive to be the 'oxymoronic status' of performance art-where it is simultaneously precarious and highly profitable-the essays in this book map the myriad gestures and radical possibilities of this extreme contradiction. This Companion adopts an interdisciplinary perspective to present performance art's legacies and its current practices. It brings together specially commissioned essays from leading innovative scholars from a wide range of approaches including art history, visual and performance studies, dance and theatre scholarship in order to provide a comprehensive and multifocal overview of the emerging research trends and methodologies devoted to performance art
Includes index (pagers [290]-305).
Keywords: Performance art; Performance arts